2017
DOI: 10.1002/ep.12674
|View full text |Cite
|
Sign up to set email alerts
|

Solvent degradation studies using hydrodynamic cavitation

Abstract: Hydrodynamic cavitation for the degradation of organic solvents was investigated in detail using a newer form of cavitating device-vortex diode. The results were also compared with that using conventional cavitating device orifice. Removal of three different organic solvents-acetone, methyl ethyl ketone (MEK), and toluene were studied on a pilot plant with capacity of 1 m 3 /h. The effect of different operating parameters such as inlet pressure, initial concentration, and reactor type on the degradation rate o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
39
0
3

Year Published

2018
2018
2022
2022

Publication Types

Select...
3
3
1

Relationship

2
5

Authors

Journals

citations
Cited by 47 publications
(47 citation statements)
references
References 33 publications
3
39
0
3
Order By: Relevance
“…This device uses swirling flow in a novel configuration to generate cavitation. This vortex based cavitation device has shown to perform better than orifice based cavitation device for variety of applications (1,20,21). The device offered 3 to 8 times better cavitational yield (mg pollutant degraded/Joules) compared to the orifice plate.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This device uses swirling flow in a novel configuration to generate cavitation. This vortex based cavitation device has shown to perform better than orifice based cavitation device for variety of applications (1,20,21). The device offered 3 to 8 times better cavitational yield (mg pollutant degraded/Joules) compared to the orifice plate.…”
Section: Introductionmentioning
confidence: 99%
“…Gogate (25) has reviewed studies reporting influence of aeration on performance of acoustic cavitation. However, studies on influence of aeration on performance of hydrodynamic cavitation are scarce (1,17). Suryawanshi et al (1) performed solvent degradation experiments and reported about 10 % increase in degradation performance in presence of aeration compared to that without aeration.…”
Section: Introductionmentioning
confidence: 99%
“…Вступ. Кавітація та її комбінації з іншими методами -основа ефективних технологій очищення стічних вод від дисперсних твердих частинок [1,2] та шкідливих органічних сполук [3][4][5][6][7][8][9][10]. Так, встановлено, що максимальної швидкості флотації кальцію оксалату, який утворювався внаслідок хімічної взаємодії натрію оксалату (протрава під час дублення шкіри) із кавітаційно активованими дисперсними частинками суспензії кальцію гідроксиду, досягали за тривалості кавітаційного оброблення 600…900 с і тиску на вході у гідродинамічний кавітатор 0,3…0,4 МПа [1].…”
Section: кавітація у комбінованих технологіях очищення стічних вод віunclassified
“…Ефективність деградації забруднювачів визначається їх початковою концентрацією у рідині (воді) [3], величиною pH [4], реаґентним режимом [4,5], енергетичними характеристиками кавітаційного оброблення (питомою потужністю ультразвукових генераторів, тиском на вході у гідродинамічні кавітатори) [6][7][8], а також конструктивними особливостями кавітаційних апаратів [9,10].…”
Section: кавітація у комбінованих технологіях очищення стічних вод віunclassified
See 1 more Smart Citation